Associations between human milk oligosaccharides (HMOs) and eating behaviour in Hispanic infants at 1 and 6 months of age. Issue 12 (3rd July 2020) - Plows, Jasmine F.; Berger, Paige K.; Jones, Roshonda B.; Yonemitsu, Chloe; Ryoo, Ji H.; Alderete, Tanya L.; Bode, Lars; Goran, Michael I.
Summary: Background: Human milk oligosaccharides (HMOs) are naturally occurring glycans in human breast milk that act as prebiotics in the infant gut. Prebiotics have been demonstrated to suppress appetite in both adults and children. Therefore, HMOs may affect infant eating behaviour. Objective: To determine if HMOs in breast milk are associated with eating behaviour in Hispanic infants. Methods: Cross‐sectional analysis of a prospective cohort of Hispanic mother‐infant dyads (1‐month, n = 157; 6‐months, n = 69). Breast milk samples were screened for 19 HMOs using high pressure liquid chromatography, and eating behaviour was assessed using the Baby Eating Behaviour Questionnaire (BEBQ). We conducted multiple linear regressions to examine associations between HMOs and BEBQ scores, adjusted for maternal pre‐pregnancy BMI, infant sex, birthweight, delivery mode and number of breastfeedings per day. We stratified by HMO secretor status—a genetic determinant of the types of HMOs produced. Results: At 1 month, LNnT (lacto‐N‐neotetraose; P = .04) was negatively associated with food responsiveness in the total sample, while DFLNT (difucosyllacto‐N‐tetrose; P = .03) and DSLNT (disialyl‐LNT; P = .04) were negatively associated with food responsiveness in secretors only. At 6 months, LSTc (sialyllacto‐N‐tetraose c; P = .01), FLNH (fucosyllacto‐N‐hexaose; P = .03), LNH (lacto‐N‐hexaose; P = .006) and DSLNH (disialyllacto‐N‐hexaose; P = .05) were positively associated with food responsiveness in both the total sample and secretors only. Conclusions: We found several HMOs that were both positively and negatively associated with infant food responsiveness, which is a measure of drive to eat.